A triple-function zwitterion for preparing water compatible diclofenac imprinted polymers. Issue 1 (12th November 2014) - Shen, Feng; Zhang, Qingxi; Ren, Xueqin
Abstract : A novel zwitterion acting as both a functional monomer and a crosslinker with the protein-resistant ability concomitantly was synthesized for preparing water compatible diclofenac imprinted polymers. This new imprinted polymer showed high imprinting efficiency for template and strong anti-protein adsorption in aqueous medium. Abstract : A novel zwitterion acting as both a functional monomer and a crosslinker with the protein-resistant ability concomitantly was synthesized for preparing water compatible diclofenac imprinted polymers. This new imprinted polymer showed high imprinting efficiency for template and strong anti-protein adsorption in aqueous medium.